Hidradenocarcinoma: A rare sweat gland neoplasm presenting as small turban tumor of the scalp - Dinesh P Asati; Swagata Brahmachari; Chandramohan Kudligi; Chandramohan Gupta (Wolters Kluwer Medknow Publications, 2015)
Hidradenocarcinomas are very rare malignant sweat gland tumors that possess an infiltrative and/or low metastatic potential. Here we describe an interesting case of hidradenoma on the fronto-parietal region of the scalp of an elderly female, part of which had developed carcinomatous changes, infiltrating up to the pericranium. She developed intense itching, pain, spontaneous ulceration and rapid increase in the size of the tumor correlating with the expression of malignant behavior of the neoplasm. An initial incision biopsy suggested features of benign poroid hidradenoma, while the histology from the excised tumor exhibited a fairly well circumscribed epithelial neoplasm in dermis consisting of interconnected nodules as well as differentiated ducts, the neoplastic cells showing mild pleomorphism of nuclei, mitotic figures and abundant pale cytoplasm. Clefts, sclerotic stroma and foci of necrosis en mass were also seen. The final diagnosis was a well differentiated and slow growing hidradenocarcinoma. The tumor recurred locally despite total excision.